Optimization Formula of Collagen Nanoemulgel from WasteMilkfish (Chanos chanos) Bones as Antiaging - Nasyanka, Anindi Lupita; Tiadeka, pemta; Nur Imtihani, Hilya; Octaviary, Niken Laras; Prastiyo, Danu (Universitas Negeri Semarang, 2024)
Climate change has negative impacts throughout the countries in the world, especially Indonesia, which has a tropical climate. Successful aging can be achieved by building individual self-confidence through prevention and skin aging. Indonesia is a producer of milkfish waste, reaching 5.4 tons/year, which is in line with the increasing center of